Неформальні інститути у процесі формування регіональних ідентичностей Донбасу - Литвин, Валентина Анатоліївна; Lytvyn, V.A. (Харків: ХНУ імені В.Н. Каразіна, 2021)
Lytvyn V. A. Informal institutions in the process of formation of regional identities in Donbas. Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in Social and Behavioral Sciences, Speciality – 052. V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2021. This thesis presents a study of the influence of informal institutions in the process of formation of regional identities in Donbas. The relevance of this study lies primarily in the emphasis on the meaning in a broad sense of the cultural component of identity, which provides a more convincing explanation of the political institutions’ formation and transformation processes through the influence of a certain cognitive set (in our case – through regional self-identification of Donbas citizens) on the strategies of choice and action of individuals in the modern Ukrainian political process. Since formal political institutions in Ukraine are ineffective, the analysis of informal practices as important sustainable components that are systematically reproduced within identities as well as determining the nature of the interaction of informal practices with formal institutions are of particular interest.
Informal institutions in the process of formation of regional identities in Donbas
У даній роботі представлено дослідження впливу неформальних інститутів у процесі формування регіональних ідентичностей Донбасу. Актуальність даного дослідження полягає передусім в акценті на значенні в широкому сенсі культурної складової ідентичності, яка дає можливість більш переконливо пояснити процес формування та реформування політичних інститутів через вплив певного когнітивного набору (у нашому кейсі – через прояви регіональних самоідентифікацій мешканців Донбасу) на стратегії вибору і дії індивідів в умовах сучасного українського політичного процесу. Оскільки формальні політичні інститути в Україні є недостатньо дієспроможними, особливий дослідницький інтерес становить аналіз неформальних практик в якості важливих стійких компонентів, що системно відтворюються в рамках ідентичностей, а також визначення характеру взаємодії неформальних практик із формальними інститутами.
Keywords: ідентичність; регіональні ідентичності; неформальні інститути; Донбас; гібридна війна; identity; regional identities; informal institutions; Donbas; hybrid war